2018
DOI: 10.1021/acs.iecr.8b01567
|View full text |Cite
|
Sign up to set email alerts
|

High Thermal Conductivity and Mechanical Properties of Nanotube@Cu/Ag@Graphite/Aluminum Composites

Abstract: Weak interfacial bonding and the agglomeration of reinforcements are critical challenges for the expected performance in thermal management materials, hindering the extensive application of aluminum matrix composites. In this work, Cu particles, nanotubes, Ag-coated graphite flakes and films, urea, and starch were mixed together to fabricate porous preforms, which then were infiltrated by vacuum gas pressure at 720 °C. The effects of graphite film thickness on the microstructure and properties of thermal condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…And, it obeys the relationship between fracture strength and porosity (Eq. ( 5)), which could be understood that the fracture strength is strongly influenced by porosity with exponential function [22]. Therefore, the flexural strength of CS-1 composite is higher than the others.…”
Section: Mechanical Performance Of Compositesmentioning
confidence: 97%
“…And, it obeys the relationship between fracture strength and porosity (Eq. ( 5)), which could be understood that the fracture strength is strongly influenced by porosity with exponential function [22]. Therefore, the flexural strength of CS-1 composite is higher than the others.…”
Section: Mechanical Performance Of Compositesmentioning
confidence: 97%
“…Hexagonal boron nitride has a layered structure, and the layers are held together by van der Waals forces between each other. The good interfacial contact between the grains of each phase is beneficial to improve the mechanical properties of composites [29][30][31]. The lamellar structure is easily deformed and filled during the sintering process, which makes the two phases more closely bonded, and the addition of sintering additives reduces the formation of defects.…”
Section: Densification and Microstructurementioning
confidence: 99%
“…The corrosion resistance of aluminum studies has been done by other researchers in the literature and it was also found that the graphene layer protects the aluminum against corrosion [14]. Moreover, Han et al [15] were fabricated nanotube@Cu/Ag@graphite/Al composite.…”
Section: Introduction *mentioning
confidence: 96%